Administrative and legal regulation of the rights of a person receiving psychiatric care - R. V. Kolodchyna; Yu. M. Domin (Bulletin of Kharkiv National University of Internal Affairs)
The scientific research is devoted to the problems of legal regulation of the rights of a person receiving psychiatric care. International legal acts, Ukrainian legislation and the works of scientists were studied. The scientific novelty of the research lies in the formulation of proposals for amendments to the current legislation. The proposed changes relate to the consolidation of the socio-economic rights of a person who receives psychiatric care, as well as the establishment of administrative responsibility for the violation of their rights. The author’s classification of the rights of a person suffering from a mental illness is given.